Síntese e caracterização de nanoestruturas de óxido de zinco por via úmida - Horta, Marla Karolyne dos Santos (2017)
In this work, wet method was used for the synthesis of ZnO nanostructured materials which were obtained by different process variables such as the precursor salt, chemical nature of the precipitating agent, concentration of the precipitating agent, use of surfactants CTAB and PEG in order to obtain materials with different morphological, structural and optical characteristics. The materials was studied by scanning electron microscopy (SEM), N2 adsorption at 77K, X-ray diffraction (XRD), X-ray fluorescence spectroscopy (FRX) and UV-visible diffuse reflectance spectroscopy (DRS). The synthesis conditions allowed to obtain different morphologies, such as nanorods, nanoflowers, nanoplates. The XRD results of ZnO samples indicated that the synthesized ZnO nanoparticles had the pure wurtzite structure (zincite) and the mixed oxide sample has two phases, zincite and tenorite. All the materials are mesoporous and the specific surfaces obtained vary from 2 to 86m 2 /g. The crystallite size of the samples are range of 6 to 57nm calculated using JADE 5.0 software. The bandgap energies obtained are within the range of 1.32 to 3.16eV. The reactivity for CO2 photoreduction with H2 was evaluated for three samples by observing the differentiated production of methanol and acetone.